PENEGAKAN HUKUM TERHADAP PELAKU BISNIS SKINCARE YANG TIDAKMEMATUHI REGULASI BPOM DI INDONESIA - Sofia, Sofia; Gultom, Elfrida Ratnawati; Rahmawan, Dhany; Indirahati, Novina Sri; Bustani, Simona (Ensiklopedia of Journal, 2025)
According to the Regulation of the Head of BPOM No. 23 of 2019 concerning Cosmetic Requirements Article 2, business actors are required to ensure that cosmetics produced for domestic distribution and/or imported for distribution in the territory of Indonesia meet the technical requirements of Cosmetic Ingredients. It is not uncommon for skincare entrepreneurs to not comply with the rules and regulations of the "Food and Drug Supervisory Agency (BPOM)." This study aims to investigate how law enforcement works against skincare businesses that violate BPOM regulations and their consequences for buyers and sellers. From the results of the research conducted by the author, the author obtained the formulation of the problem "Are there obstacles in the SKINCARE business that does not comply with BPOM in Indonesia?" and "are there obstacles in the skincare business that does not comply with BPOM in Indonesia? 'so that this study is expected to produce views and knowledge for consumers and business actors in increasing knowledge and compliance in the skincare manufacturing industry, especially in terms of compliance with applicable laws. The method used is a normative method using a "statutory approach" by reviewing and understanding the relevant literature. The results show that efficient law enforcement not only maintains consumer health, but also encourages business actors to comply with applicable parameters.Keywords: Law Enforcement, Busines Actors, Skincare, BPOM